The reproduction of difference: gender and the global division of labour. (1st April 2012) - ,
Abstract : This article starts by outlining the complex relationship between the gender division of labour in the household and the division of labour in waged work, taking account of the social, technical and spatial dimensions of this global division of labour and showing how this contradictary inter-relationship affects both the different value of men's and women's labour and the different positions that women and men occupy in the labour market. Whilst commodification and technological change have brought about shifts between work that is unpaid and work that is paid, as well as between informal and formal employment, gendered patterns continue to reassert themselves. It then goes on to introduce the contributions to this journal issue which illustrate these changing patterns and the questions they raise for future research.